Hubungan Regulasi Emosi dengan Tingkat Resiliensi pada Pasien Kanker Payudara di RSUD Bali Mandara Tahun 2025 - I Made Mertha; Komang Putriana Dewita Sari; I Ketut Suardana; Ni Made Wedri; I Wayan Sukawana; I Gusti Ketut Gede Ngurah (Jurnal Gema Keperawatan, 2026)
Breast cancer is the most common type of cancer found in women, and is the second highest cause of death from cancer worldwide. Early symptoms of breast cancer are lumps, changes in breast size, pain or swelling in the breast area. Cancer patients often experience various physical, psychological, and emotional challenges. Emotional regulation and resilience are two important psychological aspects in understanding cancer patients. The purpose of this study was to determine the relationship between emotional regulation and resilience levels in breast cancer patients at Bali Mandara Regional Hospital in 2025. This study was a quantitative study, using a descriptive correlative method, with a cross-sectional approach. Sampling used a purposive sampling technique with a sample size of 70 breast cancer patients. Data collection instruments were in the form of an emotional regulation questionnaire (ERQ) and a resilience scale (CD-RISC) that had been translated into Indonesian. Based on the results of the correlation with the Spearman Rank test, a significance value of 0,025 (p<α= 0,05) and a correlation coefficient value (r)= 0,268. This indicates a weak relationship between emotional regulation and resilience in breast cancer patients at Bali Mandara Regional Hospital in 2025. The stronger the emotional regulation, the higher the resilience in breast cancer patients.